Compactness of the Commutators of Fractional Hardy Operator with Rough Kernel (Analysis in Theory and Applications, 2022)
The more explicit decomposition of the operator and the kernel are utilized to investigate a characterization of the central $BMO(\mathbb{R}^{n})$-closure of $C_{c}^{∞}(\mathbb{R}^{n})$ space via the compactness of the commutators of fractional Hardy operator with rough kernel.